'A gente carrega a comida com a gente': consumo alimentar como processo comunicativo na convivência intercultural - Pellerano, Joana A. (2018)
This research has four main center lines: communication, consumption, food and identity. In taking food as a strong cultural and identity element, the objective of the thesis “A gente carrega a comida com a gente”: Consumo alimentar como processo comunicativo na convivência intercultural is to understand how food consumption, whether material or symbolic, can work as a communicative process with regard to identity in a situation of intercultural coexistence, especially the one experienced by people from other states of Brazil who move to the city of São Paulo (SP). The research is anchored theoretically and methodologically in cultural studies and in the notion of food as a social phenomenon that permeates all social instances. We start from a discussion about the complexity of food as a cultural and identity practice and as a communicative process in an intercultural environment, relating eating to social recognition and classification in relation to otherness; to strategies of conservation, negotiation and cultural adaptation created and shared through mediation processes; and the possibility of creating a shared cultural code. We adopted qualitative methods, notably questionnaire by interview, individual and group semi-structured interview and observation, having as subjects the “other Brazilians” of São Paulo: people who moved from other regions of Brazil to the city. Field research was carried out in 2017 and 2018, and included the interaction with a total of 65 people, who brought 90 narratives about 20 federative units from all regions of Brazil: seven narratives about the Center-West (Distrito Federal, Goiás, Mato Grosso, Mato Grosso do Sul and Tocantins), six on the North (Amapá, Amazonas and Pará), 28 on the Northeast (Alagoas, Bahia, Ceará, Maranhão, Paraíba, Pernambuco and Rio Grande do Norte), 23 on the Southeast (Espírito Santo, Minas Gerais and Rio de Janeiro) and 16 on the South (Rio Grande do Sul and Paraná). The information obtained in the field research was analyzed along with the information brought by the bibliographical research, and both serve as the basis for the reflection carried out here. The research shows that subjects use food consumption as media in intercultural coexistence, and it was possible to understand how this communicative process occurs.